Growth and Yield Response of Purple Pakcoi (Brassica rapa var. chinensis) to Shading and Watering Intervals in a Split-Plot Experiment to Support Science Literacy - Dora Fatma Nurshanti; Kenny Andika; Susanti Diana; Rofiqoh Purnama Ria; Strayker Ali Muda (Jurnal Penelitian Pendidikan IPA, 2026)
Optimization of purple pakcoi vegetable cultivation can be done through the management of environmental factors such as shade and watering intervals. This study aims to determine the effect of shade and watering intervals on the growth and yield of purple pakcoi. The experiment used a split-plot design with two factors. The main plot consisted of: N0 (no shade), N1 (50% shade), and N2 (75% shade). The subplots consisted of: P1 (watering every day), P2 (watering every 2 days), and P3 (watering every 3 days). The variables observed were: plant height, number of leaves, fresh shoot weight, dry shoot weight, fresh root weight, dry root weight, shoot-root ratio, and SPAD value. The results showed that the highest average values ​​of each variable were: plant height 34,55 cm; number of leaves 10; fresh shoot weight 96 g; dry shoot weight 3,7 g; fresh root weight 2,4 g; dry root weight 0,32 g; shoot-root ratio 14%; and a SPAD value of 38. Plants grown under 75% shade showed good tolerance to reduced light intensity. These findings suggest that purple pakcoi has the potential to be cultivated in confined urban areas and as an intercrop to improve land use efficiency.